ANALYSIS OF THE CONSTRUCTION PRINCIPLES AND PROPERTIES OF THE DEVICES FOR NEURON SIMULATION - Коlesnytskiy, Oleg; Bokcotsey, Irina; Korinniy, Anatoliy (Scientific Works of Vinnytsia National Technical University, 2015)
The paper presents classification and comparative analysis of the construction principles and properties of the known devices for neuron simulation, their drawbacks are revealed and the ways for their elimination are proposed.